Dinâmica temporal de índices de vegetação e elementos meteorológicos no café conilon - Mota, Fabrício Moulin (2015)
The remote sensing technique with the use of weather station data, has been widely studied for obtaining information about the vegetation. Highlighting the vegetation indexes through these indexes are possible to obtain information about green biomass and growth parameters and development of vegetation. This research goal was to analyze the dynamics of representative vegetation in agricultural fields (conilon coffee) in a region of São Mateus, ES, from vegetation indexes generated by the MODIS - TERRA and its relationship with meteorological data during the period 2007 to 2014. It has been used data of images of time series of NDVI (Normalized Difference Vegetation Index) and EVI (Enhanced Vegetation Index) from MODIS sensor (Moderate Resolution Imaging Spectroradiometer), and data from automatic station A616 INMET due the period of 2007 to 2014. The NDVI and EVI can be influenced by meteorological variables. The typical behavior of each index in each period was different. The meteorological variables and the EVI and NDVI can be considered a sensitive indicator to evaluate the effects of crop phenology culture. The weather variables related to NDVI and EVI showed promising results for use as an analytical indicator of vegetation.